2013
DOI: 10.1111/let.12021
|View full text |Cite
|
Sign up to set email alerts
|

Conodont chronostratigraphical resolution and Declinognathodus evolution close to the Mid-Carboniferous Boundary in the Barcaliente Formation type section, NW Spain

Abstract: The Barcaliente Formation in its type section provides significant conodont occurrences in the Mid‐Carboniferous Boundary interval (between the Mississippian and Pennsylvanian sub‐periods). A sequence of Declinognathodus morphotype appearances (considered here as species) is recognized from the uppermost Serpukhovian to the lower Bashkirian. These morphotypes belong to Declinognathodus noduliferus (Ellison & Graves) sensu lato, the primary marker for the worldwide correlation of the Mid‐Carboniferous Boundary.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The predominantly shallow‐water facies of theValdediezma Limestone are not the best facies for the record of conodonts, and thus, many samples are barren or show a low diversity compared to those of the ammonoid‐bearing nodular limestones (Sanz‐López & Blanco‐Ferrera, ). Continuous records and complete phylogenic lines are not recognized yet in this shallow‐water platform to be compared with those recorded in deep‐water facies of the region, such as those in Sanz‐López, Blanco‐Ferrera, and García‐López (), Sanz‐López et al (), and Sanz‐López, Blanco‐Ferrera, Sánchez de Posada, and García‐López ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominantly shallow‐water facies of theValdediezma Limestone are not the best facies for the record of conodonts, and thus, many samples are barren or show a low diversity compared to those of the ammonoid‐bearing nodular limestones (Sanz‐López & Blanco‐Ferrera, ). Continuous records and complete phylogenic lines are not recognized yet in this shallow‐water platform to be compared with those recorded in deep‐water facies of the region, such as those in Sanz‐López, Blanco‐Ferrera, and García‐López (), Sanz‐López et al (), and Sanz‐López, Blanco‐Ferrera, Sánchez de Posada, and García‐López ().…”
Section: Resultsmentioning
confidence: 99%
“…Upper Serpukhovian siliciclastic deep sea fan deposits above the Alba Formation are considered the first Variscan synorogenic deposit at the inner margin of the Cantabrian Zone (Julivert, ; Reuther, ). Dark limestones enriched in organic matter were deposited in most parts of the foreland basin in the late Serpukhovian and early Bashkirian times (Barcaliente Formation after Wagner, Winkler Prins, & Riding, ; see also Sanz‐López, Blanco‐Ferrera, & Sánchez de Posada, ). Progradation of the Variscan deformation associated with the emplacement of nappes caused high sedimentation rate and migration of the subsidence depocentre along the Cantabrian Zone (Marcos & Pulgar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar problems with multiple morphotypes and subspecies are also observed in the marker for the Mid‐Carboniferous boundary, the conodont Declinognathodus noduliferus , which led to a revision of all those forms (Sanz‐López et al . ). Despite these inconsistencies in L. ziegleri that have been criticized by some authors (Herbig ), others have suggested to vote for an official boundary marker of the base of the Serpukhovian (Wang et al .…”
Section: Progress In Establishing the Viséan–serpukhovian Boundary Anmentioning
confidence: 97%
“…1). For example, conodonts were a widely distributed group which suffered a marked reduction in diversity during this interval, followed by a renewed phase of evolution during Pennsylvanian time (Grayson et al 1990; Sanz-López et al 2006, 2013). The FAD of the conodont Declinognathodus noduliferus (Ellison & Graves, 1941) sensu lato , in its presumed evolutionary transition from Gnathodus girtyi simplex Dunn, 1966, was chosen to identify this important boundary (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…D. praenoduliferus Nigmadganov & Nemirovskaya, 1992 and D. bernesgae Sanz-López et al 2006 were later described as early members of the D. noduliferus group (Sanz-López & Blanco-Ferrera, 2013). As a consequence of selecting the first occurrence datum (FOD) of a very broad species grouping as the biostratigraphic tool with which the GSSP of the mid-Carboniferous boundary was picked, the boundary elsewhere has been identified using the first occurrence of any member of the D. noduliferus plexus, regardless of whether it is now considered a species or subspecies (Sanz-López et al 2013).
Figure 2. P 1 conodont element descriptive terminology.
…”
Section: Introductionmentioning
confidence: 99%